When social movements collaborate with the state towards the right to the city: Unveiling compromises and conflicts. (August 2021) - Krieger, Morgana G Martins; Pozzebon, Marlei; Gonzalez, Lauro
The right to the city represents a critique of the city as a place and an object of capitalist accumulation, in which priority is given to exchange value over use value. This critique references an ongoing and collective struggle for urban production to be radically democratic, as the expanded participation of city users would lead to appropriation, with social movements occupying a central role. This paper discusses the practices of urban social movements that cooperate with governmental institutions participating in and influencing the design and implementation of public policies. We focus on the possibilities of transformation towards the right to the city as well as the conflicts and contradictions that social movements face when partnering with the State. We carry out an in-depth investigation of two social movements involved in building housing units in Brazil as part of a federal government programme. By conceptually translating the right to the city into the economies of worth, we propose an original theoretical approach. Our study contributes to advance the understanding of the role of social movements that collaborate with governments without abandoning the goal of struggling for the right to the city. We add a pragmatic perspective to the radical conception of the right to the city by showing how different logics of action enable or hinder the possibility of the right to the city horizon. We propose that the prominence of the civic common world might transform operational processes mainly through self-management.